ISTANBUL (BOSPORUS) IMMERSED TUBE TUNNEL AND SURVEY WORKS - Yavuz, Erol (INT SCIENTIFIC CONFERENCE SGEM, 2011)
The railway lines in both sides of Istanbul have been connected to each other by an underwater tunnel passing through the Bosphorus. This type of tunnel is known as immersed tube tunnel. Immersed tube tunnel is a part of MARMARAY project that is continued nowadays. MARMARAY is a rail transport project in Istanbul. It consists of the construction of an undersea rail tunnel under the Bosphorus strait. Suburban rail lines along the Sea of Marmara from Halkali on the European side to Gebze on the Asian side will be modernized with this project. An immersed tunnel consists of several prefabricated steel shell or concrete tubes. These tubes are constructed on land. They are floated and moved to the immersion site. They are installed one by one. They are lowered and connected to one another underwater. Then, the water is pumped out and the segments are covered with the backfill materials. An immersed tunnel is generally installed in a trench that has been dredged previously in the bottom of a waterway between structures constructed in the dry. All spaces between the trench bottom and the soffit of the tunnel can be a previously prepared gravelbed, or sandbedding pumped or jetted underneath the tunnel. Piled foundations are sometimes used, where soil conditions require them. As construction proceeds, the tunnel is backfilled. The completed tunnel is usually covered with a protective layer over the roof. Survey works requires high precision in every construction project such as dam, bridge, tunnel etc. Horizontal and vertical control of tunnels are performed by using geodetic control points. Survey works should be performed precisely.
Keywords: Tunnel; Immersed Tube; Immersed Tube Tunnels; Geodetic Control; MARMARAY; Geology